Karakteristik Komposit Partikel Ijuk Mesh 100 Menggunakan Matrik Karet Dengan Komposisi 0PHR, 10PHR, 20PHR Terhadap Radiasi Sinar Gamma - Wahyudi, Sigit, Ir. Masyrukan, MT, Ir. Agus Hariyanto, MT (2016)
The purpose of this study is to determine how much gamma ray radiation absorption of the composite particles 100 mesh fibers with a rubber matrix. Composite manufacturing process begins with the preparation of materials to be used, namely: palm fiber, latex soupy with dry rubber content of 60%, ZnO, ZDEC, Ionol, sulfur. Fibers are used as filler, originally from the fibers, the fibers are made into a powder without heat treatment (treatment) that could change the nature ijuknya own. Compound made there are 3 variations for comparison, including the compound without fibers, compound with 10 phr fibers and fibers compound with 20 phr. In the manufacture of compounds, chemicals used previously done dispersion in advance so that the chemicals are homogeneous. Dispersion is carried out 24 hours and 48 hours to sulfur. Mixing of composite materials made on a glass and stirred for 15 minutes then pour in the mold with the dimensions specified. The next process of vulcanization by using an oven and heated at a temperature of 90 ° C within 1 hour. The test results can be concluded composite absorption value of the highest gamma-ray radiation to the composite particles whose composition ijuknya fibers by 20 phr with absorption of 39.71%. While the value of the composite absorption capacity against gamma radiation lowest is in no particle composite fibers, the absorption of 29.27%. Composite rubber composition larger fibers capable of absorbing radiation of gamma rays is greater than the composite rubber composition which fibers that little or no fibers. It can be concluded that the amount of the composition of the fibers is directly proportional to the absorption of gamma ray radiation tehadap, The bigger the composition of the fibers, the greater the absorbency. Conversely the smaller the composition of the fibers getting lower absorbency.